The new inflationary environment: How persistent are the current inflationary dynamics and how is monetary policy expected to respond? - Markus Demary; Anna-Lena Herforth; Jonas Zdrzalek (Institut der deutschen Wirtschaft (IW), 2022)
We argue that the period of low inflation has come to an end based on six structural factors, which define the new inflationary environment: [...] How high will inflation rise? How long will the new inflationary environment last? How challenging is it for central banks to counteract these inflationary pressures? A stagflation like in the 1970ies seems possible given these trends. The energy-crisis made the transformation of our energy systems necessary, which is, however, progressing slowly, thereby contributing to a longer lasting energy-triggered inflation. The highest risk will be an energy embargo, resulting in a deep recession together with high inflation. In this case monetary policy might be forced to inject high amounts of liquidity into markets despite high inflation.
Keywords: E31; E32; E52; 330